2019
DOI: 10.1002/bmc.4537
|View full text |Cite
|
Sign up to set email alerts
|

A liquid chromatography–tandem mass spectrometry method to simultaneously determinate dichlorvos and phoxim in tobacco

Abstract: A simple pretreatment method with liquid chromatography–tandem mass spectrometry (LC–MS/MS) was developed and validated to simultaneously determine dichlorvos and phoxim in tobacco and soil matrices. Satisfactory linearity (R2 ≥ 0.9991) of the method was obtained for both analytes. The limits of detection and limits of quantification for dichlorvos and phoxim in three matrices were 0.0015–0.006 and 0.005–0.02 mg/kg, respectively. Average recoveries were 78.24–92.21% for dichlorvos and 76.62–100.51% for phoxim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The contents of the 19 investigated components in 16 batches of samples collected from different areas are summarized in Figure . It was clear that the content of analysis compounds varied significantly among different samples, which might be due to different origins (Jiang, Kronenberg, Balick, & Kennelly, ), climatic conditions (Sleifer, Schwanz, Danielli, Apel, & Henriques, ), harvest times and processing methods (Qin et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The contents of the 19 investigated components in 16 batches of samples collected from different areas are summarized in Figure . It was clear that the content of analysis compounds varied significantly among different samples, which might be due to different origins (Jiang, Kronenberg, Balick, & Kennelly, ), climatic conditions (Sleifer, Schwanz, Danielli, Apel, & Henriques, ), harvest times and processing methods (Qin et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Dichlorvos and phoxim were analyzed with LC-MS/ MS (Qin et al, 2019). Satisfactory linearity (R 2 ≥ 0.9991) was observed for both target compounds.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…Environmental safety has become an important issue for public health and ecosystem vitality due to the harmful and detrimental consequences brought about by various pollutants emission to the environment. , Among various pollutants, organophosphorus pesticides (OPs) are a class of widely used lethal nerve agents, which can protect crops from pests and diseases in agricultural production. , However, the overuse of organophosphorus pesticides leads to high residues existing widely in food, water, and the environment. , These residual organophosphorus pesticides can irreversibly combine with the enzymes' active site of acetylcholinesterase (AChE) in living organisms to cause the buildup of neurotransmitter acetylcholine (ACh), which further poses a serious threat to human health. , Therefore, a simple, rapid, sensitive, and selective method for OP detection has become increasingly necessary. At present, there are many methods for OP detection, such as high-performance liquid chromatography, , electrochemistry, , and fluorescence. Xu et al reported the use of high-performance liquid chromatography with an ultraviolet detector for the determination of trace dichlorvos residues in foods . Qin et al developed and validated a liquid chromatography-tandem mass spectrometry to determine dichlorvos in tobacco .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Therefore, a simple, rapid, sensitive, and selective method for OP detection has become increasingly necessary. At present, there are many methods for OP detection, such as high-performance liquid chromatography, 5,6 electrochemistry, 7,8 and fluorescence. 9−11 Xu et al reported the use of high-performance liquid chromatography with an ultraviolet detector for the determination of trace dichlorvos residues in foods.…”
Section: ■ Introductionmentioning
confidence: 99%